Protective Effect and Mechanism of Edible Grass (Rumex patientia L. × Rumex tianschanicus A.LOS) Jiaosu on Alcohol-Induced Injury in HepG2 Cells - LI Xianxiu, HE Tao, MAO Yangchen, MAO Jianwei, LAI Xiaojin, SHAO Yihuai, SHA Ruyi (Shipin Kexue)
The protective effect of edible grass jiaosu (EGJ) on alcohol-induced injury in HepG2 cells was evaluated in terms of cell viability, alcohol dehydrogenase (ADH) activity, lactate dehydrogenase (LDH) activity, malondialdehyde (MDA) content and superoxide dismutase (SOD) activity. The effects of alcohol and EGJ on the metabolite profile of HepG2 cells were analyzed by gas chromatography-mass spectrometry (GC-MS), and differential metabolites and related metabolic pathways were identified to explore the protective mechanism of EGJ against alcoholic injury in HepG2 cells from a metabolomic perspective. Results showed that EGJ significantly inhibited alcohol-induced cell death by enhancing ADH and SOD activities and reducing LDH leakage and MDA content. A total of 11 intracellular and 16 extracellular differential metabolites were identified by cell metabolomics, the key intracellular metabolites were L-alanine, L-norleucine, L-proline, glycine, L-threonine and L-valine, and the key extracellular metabolites were arabitol, D-galactopyranose, glycerol monostearate, butanedioic acid and octadecanoic acid. EGJ can protect against alcoholic injury in HepG2 cells by regulating amino acid metabolism and energy metabolism. The results provide a theoretical basis for the application of EGJ as an ingredient in functional foods with hepatoprotective activity.